The Effect of The Use of Fish Flour as a Source of Protein in Complete Feeds on The Digestivenes of Fat, Crude Fiber and Nitrogen-Free Extract in Bali Cattle Fattened - Agustinus Mau Mori; Oktavianus Rafael Nahak; Paulus Klau Tahuk (BANTARA JOURNAL OF ANIMAL SCIENCE, 2022)
The study was conducted for 3 months, starting from May 13 to August 13, 2021, in the experiment cage of the Faculty of Agriculture, Universitas Timor, while the analysis of fat digestibility, crude fiber, and NFE (Nitrogen-Free Extract) was performed in the Chemical Laboratory of the Faculty of Animal Husbandry, Universitas Nusa Cendana. This study aimed to identify the effects of using fish powder as a source of protein contained in a complete feed against the fat digestibility, crude fiber, and NFE in male Bali cattle that are fattened. This study used a Completely Randomized Design (CRD) consisting of 3 treatments and 5 repetitions, so the total was 15 experimental units. The treatments given to the objects included T1= 30% Natural Lawn + 42% Corn Stove + 13% Rice Bran + 11% Brand Pollard + 4% Fish Powder, T2= 30% Natural Lawn + 42% Corn Stove + 9% Rice Bran + 11% Brand Pollard + 8% Fish Powder, and T3= 30% Natural Lawn + 42% Corn Stove + 5% Rice Bran + 11% Brand Pollard + 12% Fish Powder. The investigated variables included Fat Digestibility (%), Crude Fiber Digestibility (%), and NFE Digestibility (%). The result of the Analysis of variance showed that the crude fat digestibility and crude fiber digestibility had a significant effect (P<0.05) and the NFE digestibility did not affect significantly (P>0.05) the percentage of Fat Digestibility (T1: 19.06%; T2: 34.11%; and T3: 69.31%), Crude Fiber Digestibility (T1: 42.13%; T2: 29.02%; and T3: 18.52%), and NFE (T1: 65.01%; T2: 60.28%; and T3: 62.31%). In conclusion, the use of complete feed containing fish powder with 12% protein can increase the percentage of crude fat digestibility, while the crude fat percentage will be lower if using fish powder with 4% and 8% protein in male Bali cattle that are fattened. Meanwhile, the NFE digestibility is not affected by a different percentage of fish powder contained in complete feed.